Managing Risk in Customs : Lessons from the New Zealand Customs Service - Foley, Rebecca (World Bank, Washington, DC, 2012)
The New Zealand Customs Service's risk management system enables it to manage large volumes of cargo crossing borders with limited resources. The system encompasses a culture of problem-solving and accountability for decisions, a standard methodology for identifying and assessing risk, and an intelligence function that applies this methodology. This note highlights the fundamental principles and processes guiding the system, offering lessons for governments reforming their trade logistics functions to meet global standards and security requirements.